Analisis Pelanggaran Kode Etik Advokat Terhadap Penanganan Perkara Klien Dalam Kasus Advokat Biy Palembang - Dewanti, Tyur Reggina; Lewoleba, Kayus Kayowuan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Enforcement of the code of ethics in the legal profession is the main foundation for maintaining integrity and public trust in the law. This study examines the types of violations of the code of ethics committed by an advocate with the initials BIY in handling a case of resistance to execution, as well as the method of enforcing ethics by professional institutions. The analysis shows that BIY has exceeded the limits of the power granted by the client by unilaterally handing over the object of execution to a third party without the client's consent. This action is contrary to the principles of loyalty, honesty, and professionalism contained in the Indonesian Advocates Code of Ethics. The mechanism for enforcing ethics is carried out by the Regional Honorary Council (DKD) of PERADI South Sumatra through various stages, starting from complaints, examinations, to imposing sanctions in the form of temporary suspension for 12 months. This study shows how important objective and transparent internal supervision is to maintain the dignity of the legal profession, while also providing a deterrent effect and education for members of professional organizations. It is hoped that this process can strengthen a legal culture that has integrity and responsibility among advocates in Indonesia.